2005
DOI: 10.1021/ja054101e
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Net Addition of Arene C−H Bonds across a Ru(II)−Hydroxide Bond

Abstract: The activation of C-H bonds by transition metal complexes can proceed by multiple pathways, including the 1,2-addition of C-H bonds across early transition metal imido bonds. [1][2][3][4] Such transformations are potentially useful since subsequent N-C reductive elimination (RE) would produce a free amine; however, RE is often a high-energy reaction for early transition metals. In contrast, REs of N-C and O-C bonds form the foundation of routes to aryl amines and ethers using late transition metal catalysts. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 10 publications
(26 reference statements)
9
130
1
Order By: Relevance
“…Having observed H/D exchange at the Tp 4-positions with 1 and 5, we extended our studies to the complexes TpRu(PMe 3 ) 2 X (X ) Cl, OTf, Me, Ph, NHPh, SH, or NH 2 ). 18,21,22 Table 2 With the observation that TpRu(PMe 3 ) 2 OH (1) undergoes H/D exchange whereas TpRu(PMe 3 ) 2 Cl (7) does not initiate the H/D exchange, we heated (90°C) a 1:1 molar ratio of 1 and 7 in benzene-d 6 . Under these conditions, the 1 H NMR resonances of the Tp 4-positions of both 1 and 7 decrease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Having observed H/D exchange at the Tp 4-positions with 1 and 5, we extended our studies to the complexes TpRu(PMe 3 ) 2 X (X ) Cl, OTf, Me, Ph, NHPh, SH, or NH 2 ). 18,21,22 Table 2 With the observation that TpRu(PMe 3 ) 2 OH (1) undergoes H/D exchange whereas TpRu(PMe 3 ) 2 Cl (7) does not initiate the H/D exchange, we heated (90°C) a 1:1 molar ratio of 1 and 7 in benzene-d 6 . Under these conditions, the 1 H NMR resonances of the Tp 4-positions of both 1 and 7 decrease.…”
Section: Resultsmentioning
confidence: 99%
“…18,21,22 Some experimental efforts for TpRu(PMe3)2OH (1) have been previously described. 21 Details of computational studies of benzene C-H activation by (Tab)Ru(PH3)2-OH have been reported. 21 TpRu ( TpRu(PMe3)2OPh (5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the nitrosyl species, SBM is slightly more accessible, while OA/RE is preferred with the anionic CO analogue. 34 The major geometric differences between the SBM transition state and OA/RE intermediate are in the C-W-C angles (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) • wider in the OA intermediate) and W ◊ ◊ ◊ H distances (ca. 0.1 Å shorter in the OA intermediate).…”
Section: Sbm At L N M=cr 2 and L N M≡cr Bondsmentioning
confidence: 99%